2019
DOI: 10.3390/nu12010027
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of a Healthy Nordic Diet—From Dietary Exposure Biomarkers to Microbiota Signatures in the Metabolome

Abstract: Whole diets and dietary patterns are increasingly highlighted in modern nutrition and health research instead of single food items or nutrients alone. The Healthy Nordic Diet is a dietary pattern typically associated with beneficial health outcomes in observational studies, but results from randomized controlled trials are mixed. Dietary assessment is one of the greatest challenges in observational studies and compliance is a major challenge in dietary interventions. During the last decade, research has shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 101 publications
(158 reference statements)
1
21
0
Order By: Relevance
“…Previous intervention studies in humans showed minor effect on the metabolism of phospholipids and cholesterol (in large VLDL), after changes in the metagenomic composition induced by moderate exercise [ 90 ]. Other studies have shown correlation of metagenomics with imbalanced metabolome, resulting in a source of potential biomarkers of obesity [ 91 ], chronic obstructive disease in humans [ 92 ], the dietary effect of the insulin feeding in pigs [ 93 ], the quantifying diet effect in humans [ 94 ], or tracking a healthy dietary pattern [ 95 ]. Thus, external factors that induce changes in the microbial community, lead to changes in the metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Previous intervention studies in humans showed minor effect on the metabolism of phospholipids and cholesterol (in large VLDL), after changes in the metagenomic composition induced by moderate exercise [ 90 ]. Other studies have shown correlation of metagenomics with imbalanced metabolome, resulting in a source of potential biomarkers of obesity [ 91 ], chronic obstructive disease in humans [ 92 ], the dietary effect of the insulin feeding in pigs [ 93 ], the quantifying diet effect in humans [ 94 ], or tracking a healthy dietary pattern [ 95 ]. Thus, external factors that induce changes in the microbial community, lead to changes in the metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…These approaches, however, do not take into account other factors, either intrinsic or extrinsic, that influence the response or non-response to a dietary pattern. Important examples include the composition of gut microbiota and responsiveness to a Nordic diet, as discussed in a review paper [ 65 ], the relationship of weight loss and insulin and glucose status [ 66 ], or vitamin D responsiveness and markers of metabolic syndrome [ 67 ]. Our analysis included metabotype information as a novel feature when analyzing the association between T2DM and dietary patterns.…”
Section: Discussionmentioning
confidence: 99%
“…A strong adherence to the MD and a high intake of the food groups analyzed in this study clearly modulated the microbiota population profile toward a healthier one. Although several studies have also analyzed the effect of healthy diets, such as the Nordic [ 66 ] or the Japanese [ 67 ] diets, on gut microbiota composition, it is difficult to compare the results, as the methodologies used were different and the results may not be extrapolated from one study to another due to different classifications: enterotypes, other taxonomic levels, pathogenic bacteria, specific biomarkers, etc. In any case, the present results provide evidence for the notion that a high adherence to the MD leads to increased levels of several fiber- and carbohydrate-degrading bacterial species linked to SCFA metabolism (especially butyrate, which has an anti-inflammatory effect) that may contribute toward a healthier status.…”
Section: MD High-adherence Speciesmentioning
confidence: 99%